Tổ chức trò chơi học tập trong dạy học chủ đề “Các quy tắc tính xác suất” (Toán 11) trên nền tảng Wayground - Trang Văn Dể, Trang Văn Dể; Bùi Phương Uyên, Bùi Phương Uyên; Dương Hữu Tòng, Dương Hữu Tòng; Lê Minh Đề, Lê Minh Đề (Tạp chí Giáo dục, 2026)
In the context of current educational innovation, integrating technology into the organization of learning games in teaching is considered a strategic solution to enhance pedagogical effectiveness and promote the active and proactive participation of learners. Through learning games, students not only discover and apply knowledge naturally but also develop general competencies such as communication and collaboration skills, problemsolving and creativity skills, and information technology skills. This study presents some issues regarding learning games, the Wayground learning platform, proposes a process for organizing learning games in teaching on the Wayground learning platform, and illustrates this process through the organization of several learning games in teaching the topic “Rules of Probability Calculation” (Mathematics 11). Teachers need to select and design learning games that are linked to the lesson objectives, knowledge content, and cognitive characteristics of students; At the same time, effectively utilize the functions of the Wayground platform in organizing teaching and learning activities.